Creative Differences? Measuring Creative Economy Employment in the US and UK Using Microdata - Tom Kemeny; Max Nathan; Dave O'Brien (Institute of Labor Economics (IZA), 2018)
Using high-quality administrative microdata spanning 2011-2013, this paper develops new routines to compare creative economies using the creative trident framework, and applies them to the UK and US national and regional contexts. We find the UK creative economy is larger in workforce shares, and grows faster over the study period; the US' is absolutely larger, and is distributed more evenly across industries. Regional results are shaped by deeper differences in national urban systems. The paper highlights possibilities for widely varying national configurations of creative economies, considers potential mechanisms driving differentiation, and reflects on the usefulness of the creative trident approach.
Keywords: P50; R12; R58; L80; 330; creative industries; creative trident; cities; labour markets; occupations; cross-country analysis